Principal’s Leadership Improving Discipline of School’s Citizens - Sulastri, Sulastri (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The goal of this study was to evaluate the leadership responsibilities of the principal in enhancing student discipline. The study was carried out at SMA Negeri 3 Kayuagung. Observation, documentation, and interview-based data collection methods. The three stages of the data analysis technique are data reduction, conclusion/verification, and descriptive qualitative procedures. According to the research findings, the principal’s leadership enhances student discipline through exemplary, individual, and hierarchical ways. The SMA Negeri 3 Kayuagung residents’ motivation and complete trust from the principal has an effect on raising student discipline in academic tasks. The teacher’s example can also serve as a model for student behavior related to discipline. High-quality schools are more likely to be founded in environments where there is a culture of discipline in following rules.